2006
DOI: 10.1002/14651858.cd002982.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Psychological interventions for adults with asthma

Abstract: Kang 1993 {published data only} Kang DH. The e ects of stress, negative emotions, and psychosocial support on immune responses and symptom expression in asthmatic adolescents. Unpublished PhD Thesis, University of Wisconsin-Madison 1993. Kaptein 1987 {published data only} Kaptein AA. COPD: A challenge for the health psychologist [CARA: Een uitdaging voor de gezondheidspsycholoog]. Gedrag en Gezondheid: Tijdschri voor Psychologie & Gezondheid 1987;15(2):49-57. Kern-Buell 2000 {published data only} Kern-Buell CL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 90 publications
2
62
0
1
Order By: Relevance
“…Some assessment of family psychosocial stress using standardised questionnaires or direct interviews can be helpful. Unfortunately, the benefit of psychiatric treatment on asthma outcomes has not been wellestablished [151] and a recent Cochrane meta-analysis evaluating psychological interventions involving various relaxation and behavioural techniques both in adults and children was not able to find firm benefit of these interventions on asthma outcomes [152].…”
Section: Remarksmentioning
confidence: 99%
“…Some assessment of family psychosocial stress using standardised questionnaires or direct interviews can be helpful. Unfortunately, the benefit of psychiatric treatment on asthma outcomes has not been wellestablished [151] and a recent Cochrane meta-analysis evaluating psychological interventions involving various relaxation and behavioural techniques both in adults and children was not able to find firm benefit of these interventions on asthma outcomes [152].…”
Section: Remarksmentioning
confidence: 99%
“…Guided by written asthma action plans, some patients accept the responsibility for monitoring and adjusting their own treatment [11], whilst others fail to respond to cues for self-management [12,13] and delay important actions pending the advice of a clinician [14][15][16][17]. Novel technologies may change the dynamics of monitoring and care.…”
Section: Introductionmentioning
confidence: 99%
“…A Cochrane review of 15 randomized controlled trials of psychological interventions for adults with asthma included cognitive behavior therapy, psychoeducation, relaxation, and biofeedback. 269 Results for anxiety were conflicting, and none of the studies found significant treatment differences for depression. Drug treatments and cognitive behavior therapy 270 have been described as having some potential in patients with asthma; however, current evidence is limited, with a small number of studies and methodological shortcomings.…”
Section: Managementmentioning
confidence: 99%